Model Contextual Teaching and Learning: Does it Influence Mathematical Problem-Solving Ability and Self-Concept? - Depriwana Rahmi; Suci Yuniati; Annisah Kurniati; Mohamad Firdaus Ahmad (Pendidikan Matematika UNIMOR, 2026)
The Contextual Teaching and Learning (CTL) model is considered one of the approaches capable of integrating and simultaneously improving mathematical problem-solving abilities (KPMM). KPMM itself has a positive and significant relationship with self-concept. This research is an experiment with a factorial design. The purpose of experimental research is to determine whether or not there is an effect from the variables selected in the study. The study population includes all eighth-grade students at SMPN 40 Pekanbaru. The sample was selected using the cluster random sampling technique, resulting in class VIII A being chosen as the experimental class and class VIII B as the control class. Data collection was done thru tests, questionnaires, and observation. Data analysis was performed using a two-way ANOVA test. The research results indicate no difference in mathematical problem-solving ability (KPMM) between students who followed CTL model learning and direct instruction. However, there was a significant difference in KPMM between students with high, medium, and low self-concepts. Additionally, no interaction was found between the CTL learning model and self-concept on students' KPMM. One factor suspected of causing the lack of significant influence of the CTL model on KPMM is students' time management in solving KPMM problems, a lack of practice in solving problem-solving questions, and students' low accuracy in creating mathematical models.